Influence of Demographic Factors and Socioeconomic Status of Parents on the Level of Financial Literacy in Generation Z - Weni Andriani Eka Putri; Rosyeni Rasyid (Financial Management Studies, 2021)
This study aims to look at the influence of demogarfi factors and socio-economic status of parents on the level of financial literacy of generation Z in Padang City. The population in this study is generation Z who are in Padang City. The sample was selected using nonprobability sampling techniques. The sample obtained in this study were 200 people. The data in this study will be analyzed using multiple linear regression analysis with the SPSS program version 16.0. The results of this study are :(1) gender has no effect on the level of financial literacy (2) residence affects the level of financial literacy (3) education affects the level of financial literacy (4) age affects the level of financial literacy (5) religion has no effect on the level of financial literacy (6) parental income affects the level of financial literacy (7) paternal education has no effect on financial literacy level (8) The mother's influence on the level of financial literacy (9) of parents' work has no effect on the level of financial literacy.